Usefulness of dynamic computed tomography for diagnosing and evaluating uterine artery pseudoaneurysms in women with late post‐partum hemorrhage not complicated by retained products of conception. Issue 2 (17th January 2020) - Ogoyama, Manabu; Nakamura, Hiroyasu; Ugajin, Atsushi; Nagayama, Shiho; Suzuki, Hirotada; Takahashi, Hironori; Baba, Yosuke; Usui, Rie; Matsubara, Shigeki; Ohkuchi, Akihide
Abstract: Aim: We examined whether critical conditions, which were defined as having hemoglobin (Hb) less than 7.0 g/dL, shock index ≥1.0, or need for transfusion, were associated with the presence of extravasation (EV) on dynamic computed tomography (CT) in women with late post‐partum hemorrhage (PPH). Methods: Forty post‐partum women with late PPH without evident retained products of conception performed dynamic CT. Two radiologists retrospectively evaluated dynamic CT, and determined the presence or absence of EV and a sac‐like structure within the uterine cavity with enhancement. Results: Ultrasound images were available in 34/40 patients. Color Doppler flow in uterine cavity was evaluated in 33/34 (97%), and all women showed abnormal flow. Of 40 patients, dynamic CT revealed EV in 8 (20%), and a sac‐like structure in 30 (75%). Thus, we diagnosed these 38 (95%) as having uterine artery pseudoaneurysm (UAP). Uterine artery embolization was performed in 36/38 diagnosed as having UAP, and in 2/2 patients with an unknown cause of hemorrhage. The incidence rates of critical conditions were significantly increased in PPH women with than without EV on dynamic CT: Hb <7.0 g/dL (62.5 vs 0%, [ P < 0.001]), shock index ≥1.0 (50 vs 9.4% [ P = 0.020]), and need for transfusion (37.5 vs 0% [ P = 0.006]). Abnormal color Doppler flows were observed in all patients with either EV and sac on dynamic CT. Conclusion: Dynamic CT was useful for diagnosing UAP, and for evaluating critical conditions, in women with late PPH not complicated by retained products of conception.